Rethinking western India : the changing contexts of culture, society and religion - Deak, Dusan; Jasper, Daniel (New Delhi Orient BlackSwan, 2014)
Papers presented at the 13th International Conference on Maharashtra: Culture and Society, held in Bratislava, Slovakia in June 2010.
Includes bibliographical references (pages 251-271) and index.
Keywords: Social problems -- India -- Maharashtra -- Regional disparities -- Congresses; Religion and sociology -- India -- Maharashtra -- Regional disparities -- Congresses